AN ASSESSMENT OF THE VIETNAMESE TRANSLATION OF “THE ADVENTURES OF HUCKLEBERRY FINN - CHAPTER XX” USING HOUSE’S TRANSLATION QUALITY ASSESSMENT MODEL - Hang, Hoang Thi Diem (VNU Journal of Foreign Studies; Vol 35 No 1DO - 10.25073/2525-2445/vnufs.4336, 2019)
It is common for people to approach a foreign literary work via its translation; therefore, whether the readers can enjoy a translation text that successfully conveys the author’s intention is a concern to many researchers. In this study, with a view to assess the quality of the translation of “The Adventures of Huckleberry Finn”, the researcher utilizes the schema of Translation Quality Assessment proposed by House. The application of House’s Translation Quality Assessment shows that although the translation text achieves some success and  conveys most of the author’s message, it still reveals a number of mismatches in comparison with the source text, among which the inability to render America-African vernacular language results in a great loss of the target text. In addition, the ideational component of the translation text is also affected by overtly erroneous mistakes. On the basis of such findings, implications for literary translation are drawn.